Kewajiban Negara dalam Menjamin Harga Pangan yang Terjangkau: Kajian Normatif terhadap Prinsip Kesejahteraan Rakyat - Mardiyati, Siti (Lex Stricta : Jurnal Ilmu Hukum, 2026)
Food is a basic need and a human right that the state is obligated to fulfill, as it is included in the standard of a decent standard of living under the ICESCR. Public access to sufficient, safe, and nutritious food remains limited due to price fluctuations, particularly for low-income groups. As a welfare state, the government intervenes through price controls, subsidies, market operations, and trade policies. However, such interventions often raise legal issues and corruption risks, and are compounded by structural problems such as land conversion, the crisis of farmer succession, and the length of the distribution chain. This legal study analyzes fair price control policies based on the principles of the welfare state and formulates legal limits on intervention to prevent criminalization. The results are expected to provide legal certainty for public officials while ensuring balanced protection for farmers and consumers.